194k views
1 vote
12(x-6)=2(x-9) plzzz help

User John Whish
by
6.4k points

2 Answers

2 votes

Answer:

Explanation:

12(x−6)=2(x−9)

(12)(x)+(12)(−6)=(2)(x)+(2)(−9)(Distribute)

12x+−72=2x+−18

12x−72=2x−18

Step 2: Subtract 2x from both sides.

12x−72−2x=2x−18−2x

10x−72=−18

Step 3: Add 72 to both sides.

10x−72+72=−18+72

10x=54

Step 4: Divide both sides by 10.

10x

10

=

54

10

x=

27

5

Answer:

x=

27

5

User Ray Garner
by
6.1k points
7 votes

Answer:

x=5.4

Explanation:

12x-72=2x-18 distribute

-2x =-2x subtract

10x-72= -18

+72=+72 add

10x=54 divide

x=5.4 simplify

User Adrian Sohn
by
6.1k points